The effect of preoperative carbohydrate loading on pediatrics clinical conditions: Systematic Review - Maudyana Nisa Pranindyasari; Leny Budhi Harti (AcTion: Aceh Nutrition Journal, 2025)
Preoperative fasting was implemented to reduce the gastric residual volume (GRV) and mitigate the risk of pulmonary aspiration and hyperglycemia. Hyperglycemia can contribute to systemic infections and surgical wounds in pediatric patients, potentially extending the duration of hospitalization. Preoperative carbohydrate loading within the Enhanced Recovery After Surgery (ERAS) protocol has demonstrated efficacy in reducing the risk of postoperative complications in both adult and pediatric patients. However, scientific studies focusing on pediatric patients remain limited. This study aimed to provide a comprehensive synthesis of the effects of preoperative carbohydrate loading on preoperative GRV and pre- and postoperative blood glucose levels in pediatric surgical patients. Literature was extracted using the PRISMA method, identifying relevant studies from ScienceDirect, PubMed, Sage Journal, and ProQuest databases, using predefined keywords. Articles were screened and reviewed if they included pediatric surgical patients, were randomized controlled trials (RCTs), and had a prospective design following the PICOs model, published between 2014 and 2024. The findings indicate that preoperative carbohydrate loading does not significantly affect preoperative GRV, as evidenced by the absence of residuals (0–12,7 mL), and contributes to the stabilization of pre- and postoperative blood glucose levels (<99 mg/dL). In conclusion, preoperative carbohydrate loading is safe for pediatric patients and may serve as an optimal strategy for improving postoperative outcomes. This approach is expected to support the implementation of preoperative dietary protocols for pediatric patients in hospital settings.